No effect of schizophrenia risk genes MIR137, TCF4, and ZNF804A on macroscopic brain structure - Cousijn, H; Eissing, M; Fernández, G; Fisher, SE; Franke, B; Zwiers, M; Harrison, P; Arias-Vásquez, A (Elsevier, 2014)
Single nucleotide polymorphisms (SNPs) within the MIR137, TCF4, and ZNF804A genes show genome-wide association to schizophrenia. However, the biological basis for the associations is unknown. Here, we tested the effects of these genes on brain structure in 1300 healthy adults. Using volumetry and voxel-based morphometry, neither gene-wide effects—including the combined effect of the genes—nor single SNP effects—including specific psychosis risk SNPs—were found on total brain volume, grey matter, white matter, or hippocampal volume. These results suggest that the associations between these risk genes and schizophrenia are unlikely to be mediated via effects on macroscopic brain structure.